2008
DOI: 10.1007/s10439-008-9488-x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Coronary and Aortic Flow Waveforms

Abstract: Abstract-Empirical Mode decomposition (EMD) is a math-ematical tool designed to analyze non-stationary, non-linear stochastic waves. EMD separates a waveform into its constituent modes of oscillations or intrinsic mode functions (IMFs) and provides meaningful definitions of instantaneous frequency, instantaneous energy, mean trends and oscillation about the mean trends. This study provides a detailed mathematical analysis of blood flow waveforms in the porcine left anterior descending artery and aorta using EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Swine models are commonly used to study the mechanisms of heart failure and to develop new diagnostics and therapies. We have previously demonstrated that a biotelemetry system can reliably monitor blood flow and pressure in freely roaming normal animals [3], [8]. In the swine model, the present study demonstrated that continuous recording of pressure, flow, and electrical activity of the heart using an implantable telemetric system effectively revealed hemodynamic changes during the progression of heart failure.…”
Section: Discussionsupporting
confidence: 50%
“…Swine models are commonly used to study the mechanisms of heart failure and to develop new diagnostics and therapies. We have previously demonstrated that a biotelemetry system can reliably monitor blood flow and pressure in freely roaming normal animals [3], [8]. In the swine model, the present study demonstrated that continuous recording of pressure, flow, and electrical activity of the heart using an implantable telemetric system effectively revealed hemodynamic changes during the progression of heart failure.…”
Section: Discussionsupporting
confidence: 50%
“…It was found that the popular methods of Fourier analysis, and wavelets introduce confusing artifacts because they require the hypothesis of stationary random oscillations, and usually miss out on the nonlinear sub harmonic oscillations (22). We found Huang’s IMF method invented for study of ocean waves fits the need.…”
Section: Mathematical Expression Of Cause Functionsmentioning
confidence: 99%
“…The pressure signal was treated with the IMF method, and resolved into the mean trends and oscillations about each mean trend. A later study was carried out for blood flow which was analyzed by the IMF-Hilbert Spectrum method and compared with popular methods such as wavelet analysis and principal component analysis (22). A set of “mean trends” was obtained, each of which represents a “mean” value in a definitive sense, and together they represent the mean trend systematically with different degrees of oscilatory content.…”
Section: Mathematical Expression Of Cause Functionsmentioning
confidence: 99%
“…Computational approaches to detect miRNAs have been developed to overcome the limitation, and most methods for pre-miRNA detection are based on machine learning [5][6][7]. With the exception of few approaches based on one class classification [8][9][10], most methods rely on two class classification. While all parts contributing to model establishment are important [11], the selection of negative data is crucial since no gold standard is available.…”
Section: Introductionmentioning
confidence: 99%